Student Teachers’ Perception on the Use of Learning Community in EFL Classroom - La Sunra; Syarifah Farahdiba; Lely Novia (Celebes Journal of Language Studies, 2021)
This quantitative and qualitative study focuses on university students’ perceptions on the use of learning community through cooperative learning approach in EFL classroom. The purpose of the study is to explore the student teachers’ opinion about the use of learning community in the EFL Micro Teaching classroom. The participants of this study were the seventh semester students of the Special English Education Program taking Micro Teaching course. The number of participants was 28 students. The data were collected using questionnaire and interview. The result of this research showed that the seventh semester students of the Special English Education program of Universitas Negeri Makassar had positive responses toward the implementation of learning community through Cooperative Learning. Besides that, it was found that students were happy to attend Micro Teaching classroom which mainly consisted of group activities in learning community. Likewise, learning community helps facilitate student learning and improve their vocabulary.